Foucault pendulum at the South Pole: Proposal for an experiment to detect the Earth's general relativistic gravitomagnetic field - Braginsky, Vladimir B.; Polnarev, Aleksander G.; Thorne, Kip S. (Physical Review Letters, 1984)
An experiment is proposed for measuring the earth's gravitomagnetic field by monitoring its effect on the plane of swing of a Foucault pendulum at the south pole ("dragging of inertial frames by earth's rotation"). With great effort a 10% experiment in a measurement time of several months might be achieved.